Polyploid Nicotiana section Suaveolentes originated by hybridization of two ancestral Nicotiana clades - D’Andrea, Lucio; Sierro, Nicolas; Ouadi, Sonia; Hasing, Tomas; Rinaldi, Elijah; Ivanov, Nikolai V.; Bombarely, Aureliano (Frontiers in Plant Science, 2023)
Introduction Nicotiana section Suaveolentes is an almost all-Australian clade of allopolyploid tobacco species that emerged through hybridization between diploid relatives of the genus. In this study, we aimed to assess the phylogenetic relationship of the Suaveolentes section with several Nicotiana diploid species based on both plastidial and nuclear genes. Methods The Nicotiana plastome-based phylogenetic analysis representing 47 newly re-built plastid genomes suggested that an ancestor of N. section Noctiflorae is the most likely maternal donor of the Suaveolentes clade. Nevertheless, we found clear evidence of plastid recombination with an ancestor from the Sylvestres clade. We analyzed 411 maximum likelihood-based phylogenetic trees from a set of conserved nuclear diploid single copy gene families following an approach that assessed the genomic origin of each homeolog. Results We found that Nicotiana section Suaveolentes is monophyletic with contributions from the sections Alatae, Sylvestres, Petunioides and Noctiflorae. The dating of the divergence between these sections indicates that the Suaveolentes hybridization predates the split between Alatae/Sylvestres, and Noctiflorae/Petunioides. Discussion We propose that Nicotiana section Suaveolentes arose from the hybridization of two ancestral species from which the Noctiflorae/Petunioides and Alatae/Sylvestres sections are derived, with Noctiflorae the maternal parent. This study is a good example in which the use of genome wide data provided additional evidence about the origin of a complex polyploid clade.